Convergence or divergence patterns in income distribution across countries: A new evidence from a club clustering algorithm - Delphin Kamanda Espoir (Cogent Economics & Finance, 2022)
Since globalisation accelerated in the early 1990s, income inequality has increased in most developed countries and in some middle-income countries, including China and India. Also, inequality has declined in most countries of Latin America and the Caribbean and in many Sub-Saharan African and South Asian countries. This observation corroborates the neoclassical models of convergence that predict that, in the long-run, income distribution will tend to converge across countries. In this study, I examined whether there has been convergence in inequality between 2000 and 2015. To this end, I constructed a large panel of Gini indices of 142 countries and tested for the existence of convergence clubs using the econometric methodology proposed by Phillips and Sul. The results indicate that there is no uniform convergence to one club. Instead, I found that countries' income inequalities are converging into five different clubs. This finding is different from those reported by the few existing c ross-country studies on convergence in inequality. Furthermore, the analysis reveals strong evidence that between-club inequality increases, while within-club inequality decreases over the years. Between-club inequality is found to be determined by population growth, population density and the ratio of physical to human capital.
Keywords: O15; O47; C23; D31; R11; 330; Beta convergence; Gini index; income distribution; Log t test; club convergence